2019
DOI: 10.3748/wjg.v25.i5.622
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma: Can LI-RADS v2017 with gadoxetic-acid enhancement magnetic resonance and diffusion-weighted imaging improve diagnostic accuracy?

Abstract: BACKGROUNDThe Liver Imaging Reporting and Data System (LI-RADS), supported by the American College of Radiology (ACR), has been developed for standardizing the acquisition, interpretation, reporting, and data collection of liver imaging examinations in patients at risk for hepatocellular carcinoma (HCC). Diffusion-weighted imaging (DWI), which is described as an ancillary imaging feature of LI-RADS, can improve the diagnostic efficiency of LI-RADS v2017 with gadoxetic acid-enhanced magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In that study, five of 10 studies had only used pathology as the reference standard, which might have led to verification bias and overestimation of the probability of HCC for LR‐2 5 . In our meta‐analysis using CT/MRI LI‐RADS v2017, only one of six studies that reported the proportion of HCC for LR‐2 used pathology 13 and the other five studies used pathology and CCRS as the reference standard 12,16,18,21,24 . In addition, the definition of the LR‐2 distinctive nodule without malignant features (solid nodule <20 mm distinctive in imaging appearance compared to background nodules and with no major feature of HCC, no feature of LR‐M, and no ancillary feature of malignancy) was clearer in CT/MRI LI‐RADS v2017 4 compared to the LR‐2 cirrhosis‐associated nodule in LI‐RADS v2014, 29 which may refine the LR‐2 category so that it achieves ≤5% probability of HCC.…”
Section: Discussionmentioning
confidence: 95%
“…In that study, five of 10 studies had only used pathology as the reference standard, which might have led to verification bias and overestimation of the probability of HCC for LR‐2 5 . In our meta‐analysis using CT/MRI LI‐RADS v2017, only one of six studies that reported the proportion of HCC for LR‐2 used pathology 13 and the other five studies used pathology and CCRS as the reference standard 12,16,18,21,24 . In addition, the definition of the LR‐2 distinctive nodule without malignant features (solid nodule <20 mm distinctive in imaging appearance compared to background nodules and with no major feature of HCC, no feature of LR‐M, and no ancillary feature of malignancy) was clearer in CT/MRI LI‐RADS v2017 4 compared to the LR‐2 cirrhosis‐associated nodule in LI‐RADS v2014, 29 which may refine the LR‐2 category so that it achieves ≤5% probability of HCC.…”
Section: Discussionmentioning
confidence: 95%
“…The flow diagram of the study selection is shown in Figure 1 and the details of excluded studies are given in Supplementary Table S3 . Among 39 studies, nine records [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] demonstrated the accuracy for HCC diagnosis of CEUS LR5, and 31 [ 20 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] evaluated that of CT/MRI LR5, while eight records [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ,…”
Section: Resultsmentioning
confidence: 99%
“…The flow diagram of the study selection is shown in Figure 1 and the details of excluded studies are given in Supplementary Table S3. Among 39 studies, nine records [20][21][22][23][24][25][26][27][28] demonstrated the accuracy for HCC diagnosis of CEUS LR5, and 31 [20, evaluated that of CT/MRI LR5, while eight records [21][22][23][24][25][26][27][28] evaluated the performance of CEUS LRM for characterizing OM and 19 reported [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] that of CT/MRI LRM.…”
Section: Literature Searchmentioning
confidence: 99%
“…Inclusion of diffusion weighted imaging (DWI) increases sensitivity [39][40][41] by detecting lesions based on restricted diffusion, which is thought to reflect hypercellularity. Some DWI features may also be used to help differentiate HCC from non-HCC malignancy, such as intrahepatic cholangiocarcinoma (iCCA), which often has a more targetoid appearance [42,43] .…”
Section: Diffusion Weighted Imagingmentioning
confidence: 99%
“…Centers that elect to apply HBP-AMRI need to be aware of this potential pitfall and understand that HBP-AMRI will detect some patients with HCC precursor nodules prior to overt malignant transformation. Conversely, some reports have shown that occasionally HCCs can be iso- or hyperintense on HBP imaging and may be mistaken for benign lesions [ 15 , 23 , 40 ] .…”
Section: Hepatobilary-phase Amrimentioning
confidence: 99%